2018
DOI: 10.1104/pp.18.01343
|View full text |Cite
|
Sign up to set email alerts
|

PGR5-Dependent Cyclic Electron Flow Protects Photosystem I under Fluctuating Light at Donor and Acceptor Sides

Abstract: In response to a sudden increase in light intensity, plants must cope with absorbed excess photon energy to protect photosystems from photodamage. Under fluctuating light, PSI is severely photodamaged in the Arabidopsis (Arabidopsis thaliana) proton gradient regulation5 (pgr5) mutant defective in the main pathway of PSI cyclic electron transport (CET). Here, we aimed to determine how PSI is protected by two proposed regulatory roles of CET via transthylakoid DpH formation: (1) reservation of electron sink capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
179
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(209 citation statements)
references
References 62 publications
17
179
0
1
Order By: Relevance
“…The photoprotective role of CEF has been widely reported to participate in coping with high light, heat, and chilling stress [25]. CEF is required for both the donor-side and acceptor-side regulation and contribute to pmf formation, essential for PSI photoprotection [26,27]. Results of the present study clearly indicated that the soil salinity pretreatment is important for maintaining cyclic electron transfer around PSI.…”
Section: Discussionsupporting
confidence: 53%
“…The photoprotective role of CEF has been widely reported to participate in coping with high light, heat, and chilling stress [25]. CEF is required for both the donor-side and acceptor-side regulation and contribute to pmf formation, essential for PSI photoprotection [26,27]. Results of the present study clearly indicated that the soil salinity pretreatment is important for maintaining cyclic electron transfer around PSI.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, we recently found that the LEF rate and Fd oxidation rate have a similar relationship to that between the LEF rate and Jg [38]. These results show that ferredoxin (Fd)-dependent CEF [40][41][42][43][44][45][46] is negligibly small; that is, photosynthetic LEF is responsible for the majority of ∆pH formation [38]. The induction mechanism of ∆pH formation across the thylakoid membranes is shown in the following manner: ∆pH formation is observed as an ECS signal increase [26,47].…”
Section: Discussionmentioning
confidence: 75%
“…The recent finding that FLV functions as electron acceptor and can reduce O 2 and protect PSI from damage in gymnosperms suggests that this may be one of the key mechanisms facilitating the evergreen lifestyle of boreal conifers [32][33][34] . Angiosperms lack FLV 34,35 and heterologous expression of FLVs in angiosperms have demonstrated complementary functions of the different AEF components 18,19 . However, those measurements were performed on material grown under optimal conditions in climate chambers, similar to the summer samples in our experiments (Figs.…”
Section: Discussionmentioning
confidence: 99%